Effect of the Food Additives Sodium Citrate and Disodium Phosphate on Shiga Toxin-Producing Escherichia coli and Production of stx-Phages and Shiga toxin - Lenzi, Lucas J.; Lucchesi, Paula M. A.; Medico, Lucía; Burgán, Julia; Krüger, Alejandra (Frontiers in Microbiology, 2016)
Induction and propagation of bacteriophages along the food production chain can represent a significant risk when bacteriophages carry genes for potent toxins. The aim of this study was to evaluate the effect of different compounds used in the food industry on the growth of Shiga toxin-producing Escherichia coli (STEC) and the production of stx-phage particles and Shiga toxin. We tested the in vitro effect of lactic acid, acetic acid, citric acid, disodium phosphate, and sodium citrate on STEC growth. A bacteriostatic effect was observed in most of treated cultures. The exceptions were those treated with sodium citrate and disodium phosphate in which similar growth curves to the untreated control were observed, but with reduced OD600 values. Evaluation of phage production by plaque-based assays showed that cultures treated with sodium citrate and disodium phosphate released phages in similar o lower levels than untreated cultures. However, semi-quantification of Stx revealed higher levels of extracellular Stx in STEC cultures treated with 2.5% sodium citrate than in untreated cultures. Our results reinforce the importance to evaluate if additives and other treatments used to decrease bacterial contamination in food induce stx-phage and Stx production.